2020
DOI: 10.1097/wnr.0000000000001446
|View full text |Cite
|
Sign up to set email alerts
|

Convolvulus pluricaulis extract can modulate synaptic plasticity in rat brain hippocampus

Abstract: The memory-boosting property of Indian traditional herb, Convolvulus pluricaulis, has been documented in literature; however, its effect on synaptic plasticity has not yet been reported. Two important forms of synaptic plasticity known to be involved in the processes of memory formation are long-term potentiation (LTP) and long-term depression (LTD). In the present study, the effect of C. pluricaulis plant extract on LTP and LTD were evaluated. The adult male Wistar rats were fed orally with 250, 500 and 1000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…However, the role of each drug in psychosis have been evaluated individually. Preclinical studies have shown anti stress, nootropic and neuroprotective activity of Convolvulus [ 34 , 35 ]. All other herbs in the compound are proven to be efficacious in psychosis in distinct studies [ 25 , 27 , 30 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of each drug in psychosis have been evaluated individually. Preclinical studies have shown anti stress, nootropic and neuroprotective activity of Convolvulus [ 34 , 35 ]. All other herbs in the compound are proven to be efficacious in psychosis in distinct studies [ 25 , 27 , 30 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…These actions are likely complementary to the antioxidant mechanisms described above ( 227 ) in combatting neurodegenerative diseases. Finally, scopoletin improves neuronal plasticity, as measured in ex vivo electrophysiological assays, and exerts neuroprotective activity in a rat spinal cord injury model ( 263 , 264 ).…”
Section: Effects Of Bioactive Compounds Found In a Scopariamentioning
confidence: 99%
“…Two important forms of synaptic plasticity known to be involved in the processes of memory formation are long-term depression (LTD) and long-term potentiation (LTP). In a study, the effect of C. pluricaulis plant extract on LTP and LTD were evaluated and found that prolonged treatment of C. pluricaulis extract, at a specific dose in healthy animals, can augment memory functions by modulating hippocampal plasticity (21). A.calamus (L.) (Sweet flag), a member of the family Acoraceae, generally used alone or in combination with other herbs in Indian and Chinese traditional medicine has generated great interest and is found to be beneficial (22).…”
Section: Pluricaulis Contains D-glucose Maltose Rhamnosementioning
confidence: 99%